PURPOSE OVER PRESSURE: RETHINKING ENTREPRENEURIAL SUCCESS AND MENTAL HEALTH THROUGH IKIGAI - Mohamad, Maliani; Yusuff, Yusrinadini Zahirah Md Isa; Ab Wahab, Nur Yuhainis; Alias, Siti Nur Aisyah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Entrepreneurial discourse has traditionally been dominated by performance-driven metrics such as profit, growth, and scalability, often at the expense of entrepreneurs’ psychological health and sense of purpose. While research on entrepreneurial well-being has gained traction, there remains a lack of integrative frameworks that explicitly connect personal fulfilment with sustainable entrepreneurial success. This conceptual paper addresses this gap by proposing the Japanese philosophy of Ikigai as a theoretical lens for rethinking entrepreneurial motivation and outcomes. Drawing on positive psychology, Eastern philosophy, and entrepreneurship studies, the paper advances a model that situates entrepreneurial success at the intersection of passion, competence, social contribution, and financial viability. By reframing success through Ikigai, the paper contributes to the discourse on entrepreneurial resilience and well-being, offering a holistic pathway toward sustainable and human-centred entrepreneurship.